Is the Parallel Market Premium a Reliable Indicator of Real Exchange Rate Misalignment in Developing Countries - Ostry, Jonathan (IMF Working Papers; Working Paper, 1993)
It is often argued that the parallel market premium is a useful indicator of real exchange rate misalignment in developing countries. The empirical evidence does not, however, suggest the existence of a robust correlation between these two endogenous variables that is independent of the nature of economic shocks and various structural relationships in the economy. This paper presents an analytical investigation of the reliability of the parallel market premium as an indicator of real exchange rate misalignment in the context of a fully optimizing model of a developing country. The analysis suggests that one should exercise caution in drawing inferences about the sign and magnitude of real exchange rate misalignment from the parallel market premium.